Forecasting stroke and stroke-driven dementia in a rapidly ageing population: a model-based analysis of alternative projection scenarios for Ireland - Anne Hickey; Eithne Sexton; Frances Horgan; Kathleen E Bennett; Ronan Collins; Martin O'Flaherty; Suzanne Timmons; Chris Macey; David J. Williams (BMJ Open)
Objective Understanding future population needs is key for informing stroke service planning. This study aims to evaluate scenarios for future trends in stroke age-specific incidence and case fatality, and estimate their impact on projected stroke and poststroke dementia prevalence in Ireland.Design This is an epidemiological modelling study based on a probabilistic Markov model. We extrapolated trends in age-specific stroke incidence and case fatality from 1990 to 2019 and applied these to 2016 to 2046. We defined trend scenarios based on stability and low and high decline, broadly based on the lower and upper bounds of evidence for trends to date. We also examined nonlinear trends involving decelerating decline over time and varying trends by age.Setting/participants The study is conducted on the Irish population aged 40–89 years in the period 2022–2046. We used multiple data sources, including systematic review and observational evidence.Interventions Not applicable.Primary and secondary outcome measures We projected the incidence and prevalence of stroke (International Classification of Disease (ICD) codes I60–I61, I63–I64), poststroke dementia (Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V) criteria) and poststroke disability (modified Rankin Scale 3–5).Results The stable scenario indicated a projected 85 834 stroke survivors in 2046 (95% uncertainty interval (UI)=82 366–89 655), an increase of 45.7% from 2022. Assuming a high incidence decline and low case-fatality decline indicated a 5.4% increase in prevalence. Intermediate scenarios based on lower rates of decline, or decline rates slowing over time, implied an increase between 25.8% and 40.3%. Results did not differ substantially when we varied trends by age.In the stable scenario, we projected 16 978 poststroke dementia prevalent cases in 2046 (95% UI 14 958–19 157), an increase of 58.9% from 2022. In the high decline scenario, the increase would be 24.5%, with intermediate scenarios implying an increase between 41.3% and 56.3%.Conclusions Future stroke healthcare needs will vary substantially depending on epidemiological trends. There is an urgent need to both invest in prevention strategies and plan for likely increases in future stroke care needs.